(untitled) (Texas Journal of Engineering and Technology, 2024)
In this article, the authors studied the theoretical analysis of a mesh drum installed in the working chamber to reduce the density of the green shaft. According to it, the angles of movement are classified according to the time of changing lumps of cotton to prevent clogging of the working chamber. It is concluded that, knowing the laws of movement of cotton particles, it is possible to determine the efficiency of extracting seeds from them